ASSESSMENT OF THE IMPACT OF THE EU STRUCTURAL FUNDS ON BUSINESS IN LATVIA - Arbidane, Iluta; Tarasova, Madara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the paper is to examine the administration of EU structural funds and their influence on business development. The main problem analysed in the paper is administration of the EU structural funds and their implementation in Latvia, the impact of the activities funded by the EU funds onto business development. In the research, information about the essence and policy of the EU structural funds is analysed, including information about the aspects of formation and influence of the EU structural funds, the basic business principles and factors influencing its development, as well as funding by the EU Structural Funds as an instrument for facilitation of business development. In the research, administration of the EU structural funds, the legal framework, and an evaluation of the funds’ administration in Latvia, the activities of the EU structural funds for business development in the programming period 2007–2013, influence of the priority “Business development” upon business development in Latgale region, as well as future prospects are discussed. The aim of the paper is to examine the administration of EU structural funds and their influence upon business development. The subject of the research is the impact of EU funds onto business development. In the paper, the following research methods are used: the descriptive or monographic method, aggregation of information, analysis of documentation, statistical analysis, graphical, and the expert method. According to the obtained results, the authors conclude that the activities funded by the EU Structural Funds provide support for enterprises for innovative business development, and increase competitiveness of enterprises, as well as overall business activity.